Modeling of the flow structure in echeloned grids of stabilizers by varying their displacement step - Фиалко, Наталия Михайловна; Шеренковский, Юлий Владиславович; Прокопов, Виктор Григорьевич; Полозенко, Нина Петровна; Меранова, Наталья Олеговна; Алешко, Сергей Александрович; Иваненко, Геннадий Владимирович; Юрчук, Владимир Леонидович; Милко, Евгений Иванович; Ольховская, Нина Николаевна (Eastern-European Journal of Enterprise Technologies, 2015)
The paper deals with investigating the fuel and oxidizer flow patterns in the ladder echeloned grids of flame stabilizers by varying their displacement step relative to each other along the flow. Based on the mathematical modeling, the effects of the specified step on the redistribution nature of the air flows in stabilizer grid channels were studied, and the fact of the flow pattern asymmetry increase with the displacement step increase was established. The analysis of the features of the circulation flow in the near wake of stabilizers at different values of their displacement step along the flow was performed. The results of investigations on determining the influence patterns of the stabilizer displacement step on pulsating flow characteristics were presented. It was found that an increase of this step causes a significant reduction in velocity fluctuations in astern stabilizer areas. Studies on determining the dependence of the pressure loss on the stabilizer displacement step in the considered stabilizer-type burner device were performed. It is shown that specified pressure losses are reduced considerably with displacement step increase.